2021
DOI: 10.1111/1462-2920.15763
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in surface‐sensing receptor WspA lock the Wsp signal transduction system into a constitutively active state

Abstract: Pseudomonas aeruginosa rugose small-colony variants (RSCVs) are frequently isolated from chronic infections, yet, they are rarely reported in environmental isolates. Here, during the comparative genomic analysis of two P. aeruginosa strains isolated from crude oil, we discovered a spontaneous inframe deletion, wspA Δ280-307 , which led to hyperbiofilm and RSCV phenotypes. WspA is a homologue of methyl-accepting chemotaxis proteins (MCPs) that senses surfaces to regulate biofilm formation by stimulating cyclic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…wspR deletion abolishes the function of Wsp system, whereas wspF deletion locks Wsp system in a constantly activated state in which WspR is continuously phosphorylated to produce c‐di‐GMP (Güvener and Harwood, 2007; Huangyutitham et al ., 2013). Previous studies have revealed that surface growth activates Wsp system, thus resulting in biofilm formation (Güvener and Harwood, 2007; O'connor et al ., 2012; López‐Farfán et al ., 2019; Hueso‐Gil et al ., 2020; Xu et al ., 2021). More recently, Wsp system has been reported to mediate c‐di‐GMP heterogeneity during surface sensing, leading to two physiologically distinct cell subpopulations (Armbruster et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…wspR deletion abolishes the function of Wsp system, whereas wspF deletion locks Wsp system in a constantly activated state in which WspR is continuously phosphorylated to produce c‐di‐GMP (Güvener and Harwood, 2007; Huangyutitham et al ., 2013). Previous studies have revealed that surface growth activates Wsp system, thus resulting in biofilm formation (Güvener and Harwood, 2007; O'connor et al ., 2012; López‐Farfán et al ., 2019; Hueso‐Gil et al ., 2020; Xu et al ., 2021). More recently, Wsp system has been reported to mediate c‐di‐GMP heterogeneity during surface sensing, leading to two physiologically distinct cell subpopulations (Armbruster et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To further explore this assumption, we used a PAO1-derived RSCV mutant, PAO1Δ wspF , 24 to assess RLs production during fermentation. Consistent with KT1115, PAO1Δ wspF showed a considerable period of high biofilm exopolysaccharides production from 0 to 96 h ( Figures 3 A and S1 B).…”
Section: Resultsmentioning
confidence: 99%
“…WspR has a REC domain fused to the GGDEF domain, and phosphorylation of this REC domain enhances its DGC activity 17 , 18 . Previous studies found that inactivation of wspF in P. aeruginosa , which encodes an ortholog of E. coli CheB methylesterase, resulted in elevated intracellular c-di-GMP level and the formation of a wrinkly colony phenotype, thereby promoting biofilm formation 17 , 19 , 20 . In the wspF mutant background, this effect is caused by enhanced DGC activity of WspR through WspE phosphorylation 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that inactivation of wspF in P. aeruginosa , which encodes an ortholog of E. coli CheB methylesterase, resulted in elevated intracellular c-di-GMP level and the formation of a wrinkly colony phenotype, thereby promoting biofilm formation 17 , 19 , 20 . In the wspF mutant background, this effect is caused by enhanced DGC activity of WspR through WspE phosphorylation 20 , 21 . Therefore, it was found that blockade of the methylesterase WspF artificially alters Wsp signaling from a locked state to an activated state by increasing intracellular c-di-GMP levels 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation